On a question of Wiegold and torsion images of Coxeter groups - Grigorchuk, R. (Algebra and Discrete Mathematics, 2009)
We answer positively a question raised byWiegold in Kourovka Notebook and show that every Coxeter group that is not virtually abelian and for which all labels in the corresponding Coxeter graph are powers of 2 or infinity can be mapped onto uncountably many infinite 2-groups which, in addition, may be chosen to be just-infinite, branch groups of intermediate growth.